MENGUKUR EFEKTIFITAS TEKNOLOGI INFORMASI DALAM MENUNJANG KOMPETENSI SDM DALAM PENINGKATAN KINERJA UMKM MAKANAN RINGAN DI KABUPATEN MAGELANG - Achmad Bayu Kurniawan; Nia Kurniati Bachtiar (Prosiding University Research Colloquium, 2022)
This study aims to measure the effectiveness of Information Technology (IT) as a mediation in supporting the competence of Human Resources (HR) in improving the performance of snack food SMEs in Magelang district. The population in this study is SMEs snack in Magelang district. The samples taken in this study were 100 with the Lemeshow formula because of the limited data on the number of Snack SMEs population at the research location. The analytical tool used is multiple regression with the help of SPSS 25, the results of this study show that HR competence has a positive and significant effect on MSME performance by 48.6%, but HR competency and IT only has an effect of 23.5% on MSME performance. This shows that the effectiveness of IT on the performance of MSMEs is not as high as imagined and this study will provide the argument.